The complex relationship between vitamin D and kidney stones: balance, risks, and prevention strategies - Zhang, Fan; Li, Wenjian (Frontiers in Nutrition, 2024)
The association between vitamin D and kidney stones is characterized by a remarkable multi-dimensional complexity involving numerous physiological and metabolic pathways. Vitamin D is pivotal in maintaining calcium-phosphorus metabolic homeostasis and bone health. However, fluctuations in its intake, whether excessive or insufficient, may potentially increase the risk of kidney stones. Vitamin D exerts its influence on kidney stone formation indirectly by increasing the efficiency of intestinal calcium absorption and regulating renal calcium excretion. Moreover, there is a robust correlation between various states of vitamin D, particularly its active form, 1,25-dihydroxyvitamin D, and the development of numerous kidney stones. This finding underscores the necessity of individualized medical treatment in vitamin D supplementation and kidney stone prevention. When developing treatment strategies, it is essential to consider the patient's genetic background, lifestyle, environmental factors, and overall health. To prevent the formation of kidney stones, it is recommended that patients adopt a comprehensive approach, which may include measures such as moderate sun exposure, dietary modification, moderate exercise, and weight management. These preventive measures are designed to maintain healthy calcium and phosphorus metabolism and reduce kidney stone formation risk. Future studies should aim to elucidate the detailed mechanisms of vitamin D metabolism, individual differences, and the role of genes in this process. Furthermore, the role of lifestyle interventions in preventing kidney stones requires greater attention. Moreover, the implementation of large-scale, long-term prospective studies and randomized controlled trials will facilitate the assessment of the actual effects of diverse vitamin D supplementation strategies, thereby providing a robust scientific foundation for advancing more precise prevention strategies and clinical guidelines.